Physiological and genomic characterisation of Saccharomyces cerevisiae hybrids with improved fermentation performance and mannoprotein release capacity - Pérez Través, Laura (2015)
Yeast mannoproteins contribute to several aspects of wine quality by protecting wine against protein haze, reducing astringency, retaining aroma compounds and stimulating lactic-acid bacteria growth. The selection of a yeast strain that simultaneously overproduces mannoproteins and presents good fermentative characteristics is a difficult task. In this work, a Saccharomyces cerevisiae × S. cerevisiae hybrid bearing the two oenologically relevant features was constructed. According to the genomic characterisation of the hybrids, different copy numbers of some genes probably related with these physiological features were detected. The hybrid shared not only a similar copy number of genes SPR1, SWP1, MNN10 and YPS7 related to cell wall integrity with parental Sc1, but also a similar copy number of some glycolytic genes with parental Sc2, such as GPM1 and HXK1, as well as the genes involved in hexose transport, such as HXT9, HXT11 and HXT12. This work demonstrates that hybridisation and stabilisation under winemaking conditions constitute an effective approach to obtain yeast strains with desirable physiological features, like mannoprotein overproducing capacity and improved fermentation performance, which genetically depend of the expression of numerous genes (multigenic characters).